Disasterization: A Simple Way to Fix the Asset Pricing Properties of Macroeconomic Models - Gabaix, Xavier (American Economic Review, 2011)
A central difficulty in economics is to create a model with both good business cycle properties and asset pricing properties. I show how to solve this difficulty by a simple portable modeling device: the “disasterization” of models. Take an economy with good business cycle properties and create a new, “disasterized” economy, which is essentially identical to the original one except that disasters can destroy part of the capital stock and productivity. In such a disasterized economy, asset prices exhibit high and volatile risk premia, but macro variables remain unchanged. Perturbations of this benchmark allow for feedback from finance to macro.